2022
DOI: 10.3389/fmed.2022.751636
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation in Patients With Severe COVID-19 Associated With Sepsis and Septic Shock

Abstract: BackgroundNeuromuscular electrical stimulation (NMES) can be applied to critically ill patients. However, its results on muscle strength and functionality in patients with COVID-19 are unknown.ObjectiveEvaluate the effects of intervention with NMES on muscle mass and functionality of patients with severe COVID-19 associated with sepsis and septic shock.MethodsSeven patients with COVID-19 associated with sepsis or septic shock were selected, but only 5 patients completed all days of the intervention with NMES. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
6
0
3
Order By: Relevance
“…Electrical stimulation is known to excite motor units that are used for greater levels of force production ( 49 ), aiding lower-extremity muscle strength preservation for voluntary activation ( 50 ). In a recent prospective cohort study in ( n = 5) ICU COVID-19 patients, Righetti et al stated daily E-Stim to the quadricep muscles in mechanical ventilated patients is feasible at improving strength at 5 and 8 days per interrupted sedation assessment ( 21 ). Similar non-COVID population studies utilizing E-Stim to the peroneus longus ( n = 24) ( 51 ) and anterior tibialis ( n = 11) ( 52 ) found a significant improvement in ankle dorsiflexion strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrical stimulation is known to excite motor units that are used for greater levels of force production ( 49 ), aiding lower-extremity muscle strength preservation for voluntary activation ( 50 ). In a recent prospective cohort study in ( n = 5) ICU COVID-19 patients, Righetti et al stated daily E-Stim to the quadricep muscles in mechanical ventilated patients is feasible at improving strength at 5 and 8 days per interrupted sedation assessment ( 21 ). Similar non-COVID population studies utilizing E-Stim to the peroneus longus ( n = 24) ( 51 ) and anterior tibialis ( n = 11) ( 52 ) found a significant improvement in ankle dorsiflexion strength.…”
Section: Discussionmentioning
confidence: 99%
“…While it may be a suitable treatment to facilitate the rehabilitation pathways for COVID-19 patients ( 20 ), empirical evidence is needed ( 11 ). Today, this technology has been demonstrated to improve muscle strength in ICU COVID-19 patients ( 21 ). However, there is still a lack of randomized studies ( 22 ) to confirm its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…This therapy has been shown to improve muscle endurance in hospitalized or limited‐mobility patients (Burgess et al, 2021), to reduce muscle loss (Burgess et al, 2021; Leite et al, 2018), and improve tissue perfusion (Zulbaran‐Rojas et al, 2021). Additionally, E‐Stim has been effective in improving muscle strength (Righetti et al, 2022) and endurance (Zulbaran‐Rojas et al, 2022) in severe acute COVID‐19 patients. However, the long‐term effects of E‐Stim on muscle perfusion have not been well studied, and its utility for the recovery of individuals with musculoskeletal PASC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous RCT, application of EMS to the gastrocnemius muscles for up to 14 days was accompanied only by improvements in lower extremity muscle condition, e.g., ankle muscle strength and endurance, in critically ill patients with COVID-19 admitted to the ICU 30 . In another study, application of EMS to the quadriceps femoris muscles for 7 consecutive days only increased muscle strength assessed according to the MRC score and function in patients with severe COVID-19 during ICU admission, although they did not include a control group for comparison 31 . The results of the present study indicated that the application of EMS to the biceps brachii, quadriceps femoris, and gastrocnemius muscles for up to 2 weeks (median 5 days) was not accompanied by a decrease in occurrence of ICU-acquired weakness (i.e., MRC score < 48 points) and improved physical function and mobility at discharge from the ICU in patients with COVID-19 requiring IMV.…”
Section: Discussionmentioning
confidence: 98%